2022
DOI: 10.3389/fpubh.2022.841770
|View full text |Cite
|
Sign up to set email alerts
|

Nurse's Psychological Experiences of Caring for Severe COVID-19 Patients in Intensive Care Units: A Qualitative Meta-Synthesis

Abstract: BackgroundCOVID-19 has been listed as an international public health emergency. During the pandemic, the nurses were affected physically and mentally when in contact with and caring for patients infected with COVID-19, especially those in intensive care units (ICUs).ObjectiveTo summarize and evaluate the actual psychological experience of nurses caring for patients with severe pneumonia in the ICUs during the COVID-19 pandemic.MethodsRelevant publications were identified by systematic searches across 11 databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Studies have shown that psychological adaptation and social support are intermediate in psychological rehabilitation under outbreak stress (Mak et al, 2009 ). A meta‐analysis of nurses' experiences caring for patients in intensive care units indicated that they needed support from friends and families when caring for patients during COVID‐19 (Han et al, 2022 ). In this study, participants reported that they resorted to their families and friends for strength and support.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that psychological adaptation and social support are intermediate in psychological rehabilitation under outbreak stress (Mak et al, 2009 ). A meta‐analysis of nurses' experiences caring for patients in intensive care units indicated that they needed support from friends and families when caring for patients during COVID‐19 (Han et al, 2022 ). In this study, participants reported that they resorted to their families and friends for strength and support.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several qualitative systematic and scoping reviews have reported the concerns and the vulnerability perceived by nurses. [6][7][8][9][10][11] Overall, studies have highlighted their experiences regarding the poor organizational support, the lived difficulties in wearing personal protective equipment (PPE), the physical symptoms experienced (e.g. insomnia, headache, and fatigue) and the frustration of not being able to read up on the best evidence about COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…insomnia, headache, and fatigue) and the frustration of not being able to read up on the best evidence about COVID-19. [6][7][8][9][10][11] In addition, nurses have reported experiencing psychological exhaustion as fear (e.g. of being infected and infecting their acquaintances), depression, anxiety and feelings of helplessness and uncertainty, as well as post-traumatic and workrelated stress disorders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations